PELATIHAN PEMBUATAN POPCORN CARAMEL DAN PENGEMASAN DI KELURAHAN TOGO-TOGO KAB. JENEPONTO - Bahtiar, Akbar; Marsa, Marsa; Susanto, Cucut; Nurdiansah, Nurdiansah (Yayasan Education and Social Center, 2023)
This research aims to provide training to the community in Togo-Togo Village, Jeneponto Regency, in making caramel popcorn and its packaging, giving participants skills in producing high quality caramel popcorn which can be sold as a ready-to-eat food product. The method used in this training is a practical approach that involves participants directly in the process of making caramel popcorn. Participants will be taught about selecting good corn kernels, techniques for making caramel, processing popcorn properly, and attractive packaging. It is hoped that the results of this research will provide benefits to the people of Togo-Togo Village. With this training, it is hoped that participants can develop their skills in making quality caramel popcorn that can be sold commercially. This is expected to increase their income and make a positive contribution to the local economy. Especially in Togo-Togo Village, Jeneponto Regency, it can provide benefits to the local community. With this training, it is hoped that it can encourage the development of micro businesses and improve the economy in the district. Jeneponto